Acute Liver Failure: From Textbook to Emergency Room and Intensive Care Unit With Concomitant Established and Modern Novel Therapies. Issue 2 (February 2019) - Doulberis, Michael; Kotronis, Georgios; Gialamprinou, Dimitra; Özgüler, Onur; Exadaktylos, Aristomenis K.; Oikonomou, Vasileios; Katsinelos, Panagiotis; Romiopoulos, Iordanis; Polyzos, Stergios A.; Tzivras, Dimitri; Deretzi, Georgia; Dardiotis, Efthimios; et al.
Abstract : Acute liver failure is a rare hepatic emergent situation that affects primarily young people and has often a catastrophic or even fatal outcome. Definition of acute liver failure has not reached a universal consensus and the interval between the appearance of jaundice and hepatic encephalopathy for the establishment of the acute failure is a matter of debate. Among the wide variety of causes, acetaminophen intoxication in western societies and viral hepatitis in the developing countries rank at the top of the etiology list. Identification of the clinical appearance and initial management for the stabilization of the patient are of vital significance. Further advanced therapies, that require intensive care unit, should be offered. The hallmark of treatment for selected patients can be orthotopic liver transplantation. Apart from well-established treatments, novel therapies like hepatocyte or stem cell transplantation, additional new therapeutic strategies targeting acetaminophen intoxication and/or hepatic encephalopathy are mainly experimental, and some of them do not belong, yet, to clinical practice. For clinicians, it is substantial to have the alertness to timely identify the patient and transfer them to a specialized center, where more treatment opportunities are available.